Case Study of Progressive Muscle Relaxation Intervention to Reduce Pain in Appendicitis Patients - Lilis Lismayanti; Haryani Haryani; Aditya Nur Wahyuni; Iman Masluh Aziz (Genius Journal, 2023)
Objective: This case study was conducted to describe a progressive muscle relaxation intervention in reducing pain in appendicitis patients. Methods: This study uses a case study design with an evidence-based practice approach that focuses on nursing interventions. This research was conducted at the BLUD RSU Banjar City on 27-31 May 2022. Participants in this study were Ny patients. C, 35 years old, female, complains of right lower quadrant abdominal pain. The process of assessing and establishing a diagnosis is focused on the main problem. Objective and subjective data becomes a reference for periodic evaluation of nursing implementation. Results: Patients gave recognition of decreased pain after being given a progressive muscle relaxation intervention with a pain scale of 4 out of 5 (0-10) and a scale of 3 out of 4 (0-10).   Conclusion: Progressive muscle relaxation intervention should be suspected to be effective in reducing pain in appendicitis patients as evidenced by subjective patient recognition. Theoretically, this study does not conflict with previous research so that it can be a reference in future research. Theoretically, this research does not conflict with previous research so that it can be a reference in future research. Clinically, progressive muscle relaxation intervention can be an alternative intervention to reduce pain levels in patients with chronic diseases such as appendicitis in hospitals and health centers.